GUIDELINES FOR EFFECTIVE USE OF CORPORATE BONDS IN THE DEVELOPMENT OF THE CAPITAL MARKET (E Global Congress, 2024)
Along with developing countries, Uzbekistan also has many untapped opportunities in economic and financial processes, such as economic development and stabilization of the financial market. In particular, the attraction of financial resources from the capital market by means of new types of bonds in the financial market serves the emergence of long-term debt obligations in the financial market, and as a result of the use of the generated funds in the production and service sector, creating additional value. helps to increase. In particular, the issuance of Eurobonds, green bonds, and municipal bonds in the bond market by the issuers of our country creates the basis for the emergence of new opportunities for attracting financial resources through bonds. The transfer of the funds raised for the placement of the first sovereign Eurobonds to commercial banks is not of strategic importance and serves only to cover the costs associated with the placement and payment of interest. In our view, the capital value of Eurobonds should be disclosed so that sovereign or corporate Eurobond placements can serve as a benchmark for other issuers. It can be said that the issuance of sovereign bonds in 20191 was a test experiment for Uzbekistan. After that, the issuance of sovereign bonds on behalf of the Republic of Uzbekistan is accelerating. This, in turn, will be directed to the effective use of the proceeds from the placement of international bonds of our country, including the financing of investment projects of strategic importance in further improving the welfare of the country and our people.